2021
DOI: 10.48550/arxiv.2102.08549
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

First Target and Opinion then Polarity: Enhancing Target-opinion Correlation for Aspect Sentiment Triplet Extraction

Abstract: Aspect Sentiment Triplet Extraction (ASTE) aims to extract triplets from a sentence, including target entities, associated sentiment polarities, and opinion spans which rationalize the polarities. Existing methods are short on building correlation between target-opinion pairs, and neglect the mutual interference among different sentiment triplets. To address these issues, we propose a novel two-stage method which enhances the correlation between targets and opinions: at stage one, we extract targets and opinio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
14
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(14 citation statements)
references
References 29 publications
0
14
0
Order By: Relevance
“…5 As shown in Table VI, firstly, Both, OnlyTab and [14] outperforms OnlySeq and GTS, which shows the importance of compositional feature for ASTE. Secondly, our OnlyTab model outperforms [14] on three of four datasets. which shows our table encoder is relatively better to capture the compositional feature than [14].…”
Section: B Effect Of Table Encodermentioning
confidence: 91%
See 4 more Smart Citations
“…5 As shown in Table VI, firstly, Both, OnlyTab and [14] outperforms OnlySeq and GTS, which shows the importance of compositional feature for ASTE. Secondly, our OnlyTab model outperforms [14] on three of four datasets. which shows our table encoder is relatively better to capture the compositional feature than [14].…”
Section: B Effect Of Table Encodermentioning
confidence: 91%
“…Secondly, our OnlyTab model outperforms [14] on three of four datasets. which shows our table encoder is relatively better to capture the compositional feature than [14]. In addition, we also conduct a case study to intuitively show the effect of our table encoder, as shown in Figure 7, the top-right and bottom-left triangles of the matrix represent the sentiment classification results of OnlyTab and OnlySeq, respectively.…”
Section: B Effect Of Table Encodermentioning
confidence: 91%
See 3 more Smart Citations